Pre-Service English Teachers' Voices About the Teaching Practicum - Jairo Enrique Castañeda-Trujillo; Ana Jackelin Aguirre-Hernández (Asociación Colombiana de Profesores de Ingles, 2018)
This paper shows the results of a pedagogical experience with a group of pre-service English teachers during their first semester of teaching practicum. The data were collected by means of reflection papers written by them, and then the resulting papers were analyzed under the principles of codification of grounded theory. The results show that pre-service English teachers develop a sense of awareness of the context they work on. Also, the mentor teacher is important in such understanding, because she or he provides theories and personal experiences that contribute to the reflection. Finally, we conclude that pre-service teachers' reflections could contribute to curriculum development, so, it is advisable that language teacher education programs provide the mechanisms to give them a voice.